Review of lexical availability studies in Bolivia, Peru, Ecuador and Venezuela - Herranz-Llácer, Cristina V. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article shows the results of a systematic literature review on lexical availability in Bolivia, Peru, Ecuador, and Venezuela. The Dialnet, Scielo, Google Scholar and DispoLex platforms were used for the proper development of the research. With the data collected, it was possible to infer that scientific production on this subject is recent. However, this does not imply that the publications can be considered irrelevant. On the contrary, thanks to them, plans have been proposed to promote reading, the analysis of vocabulary related to new technologies or, for example, the use of new web tools.